The microbiology and volatile acid analysis of fermented anchovy (Stolephorus commersonii) with added rice (Tinomayan Bolinao) - Oronan, Ma. Asuncion Valenzuela
"Fermented fish with added rice" (tinomayan) is a high salt fermented product prepared from either siganid fry or small anchovy. The fermentation process involves an initial ferementation stage which includes salting of the fish and fermentation of the fish-salt mixture for fifteen days. A final fermentation stage follows wherein, the fermented fish is a mixed with cooked rice and allowed to complete fermentation at ambient temperatures. The changes in pH during the initial fermentation stage where characterized by a continual decrease during the first week of fermentation, and was followed by an increasing trend on the second week. The pH values decreased steadily during the final fermentation stage. These changes in the pH values of the fermenting fish were complemented with a general increase in titrable acidity values with fermentation time. Microbiological investigation revealed an overlapping growth of two groups of salt-tolerant bacteria -- Micrococcus sp. and Pediococcus sp., during the initial fermentation stage. A sequential but overlapping growth of lactic acid bacteria was observed on the final stage of fermentation. The Streptococci, which appeared one day after the addition of cooked rice, were outnumbered by the Leuconostocs after two days. The Pediococci coexisted with the Leuconostocs and were noted to have dominated the microflora of the fermenting mixture. lactobacillus strains, which were mostly low-acid producing atypical colonies, appeared later but did not exhibit a major role in the fermentation process. Qualitative and quantitative analyses of the volatile organic acids by gas chromatography revealed that acetic acid in fermenting anchovy with added rice (tinomayan bolinao). Propionic acid, n-butyric acid, iso-butyric acid and iso-valeric acid were also detected at low concentrations. The role of microorganisms in the production of volatile organic acids was determined by pasteurization treatment and pure culture inoculations. It was observed that innoculations with Pediococcus sp. yielded total volatile acid values which approximate the values obtained from uninoculated lot.